Motor expertise modulates unconscious rather than conscious executive control - Meng, Fanying; Li, Anmin; You, Yihong; Xie, Chun (PeerJ, 2019)
Background Executive control, the ability to regulate the execution of a goal-directed task, is an important element in an athlete’s skill set. Although previous studies have shown that executive control in athletes is better than that in non-athletes, those studies were mainly confined to conscious executive control. Many recent studies have suggested that executive control can be triggered by the presentation of visual stimuli without participant’s conscious awareness. However, few studies have examined unconscious executive control in sports. Thus, the present study investigated whether, similar to conscious executive control, unconscious executive control in table tennis athletes is superior to that in non-athletes. Methods In total, 42 age-matched undergraduate students were recruited for this study; 22 nonathletic students lacking practical athletic experience comprised one group, and 20 table tennis athletes with many years of training in this sport comprised a second group. Each participant first completed an unconscious response priming task, the unconscious processing of visual-spatial information, and then completed a conscious version of this same response priming task. Results Table tennis athletes showed a significant response priming effect, whereas non-athletes did not, when participants were unable to consciously perceive the visual-spatial priming stimuli. In addition, the number of years the table tennis athletes had trained in this sport (a measure of their motor expertise) was positively correlated with the strength of the unconscious response priming effect. However, both table tennis athletes and non-athletes showed a response priming effect when the primes were unmasked and the participants were able to consciously perceive the visual-spatial priming stimuli. Conclusion Our results suggest that motor expertise modulates unconscious, rather than conscious, executive control and that motor expertise is positively correlated with unconscious executive control in table tennis athletes.
Keywords: Motor expertise; Unconscious executive control; Conscious executive control; Table tennis athletes